2004
DOI: 10.1038/sj.ijo.0802608
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase in the prevalence of obesity in elementary school children

Abstract: OBJECTIVE: Three critical periods have been suggested for the development of obesity during childhood: fetal, ages 4-6 y, and adolescence. The prevalence of obesity in elementary school children is increasing in Japan, and the present study examines whether this rising prevalence occurs during the elementary school period (age 6-11 y) or is occurring prior to entry into elementary school. DESIGN: Repeated cross-sectional sampling of cohorts of children for the prevalence of obesity. SETTING AND PARTICIPANTS:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 19 publications
3
34
2
1
Order By: Relevance
“…25 Risk factor accumulation associated with lifestyle changes and the increased number of obese youths are becoming more serious health problems in Japan as well as in Western countries. 26,27 Concomitant Medical Therapies in Patients Aged ≤55 Years or >55 Years The practice patterns for medical therapies at hospital discharge were quite similar and the prescription rates of major preventive medicines for CAD, including anti-platelets, ACEI/ARB and β-adrenergic blockers, were comparable between the patients aged ≤55 years and those aged >55 years, except for a significantly higher prescription rate of statins in the younger patients. Considering the possibility of lower prevalences of comorbidities that might limit the use of drugs in older patients, the medical therapies for secondary prevention of CAD in younger patients might not have been optimal in real-world practice in Japan from 2000 to 2002.…”
Section: Accumulation Of Metabolic Risk Factors In Young Cad Patientsmentioning
confidence: 96%
“…25 Risk factor accumulation associated with lifestyle changes and the increased number of obese youths are becoming more serious health problems in Japan as well as in Western countries. 26,27 Concomitant Medical Therapies in Patients Aged ≤55 Years or >55 Years The practice patterns for medical therapies at hospital discharge were quite similar and the prescription rates of major preventive medicines for CAD, including anti-platelets, ACEI/ARB and β-adrenergic blockers, were comparable between the patients aged ≤55 years and those aged >55 years, except for a significantly higher prescription rate of statins in the younger patients. Considering the possibility of lower prevalences of comorbidities that might limit the use of drugs in older patients, the medical therapies for secondary prevention of CAD in younger patients might not have been optimal in real-world practice in Japan from 2000 to 2002.…”
Section: Accumulation Of Metabolic Risk Factors In Young Cad Patientsmentioning
confidence: 96%
“…The growing prevalence of childhood obesity [1][2][3][4][5] highlights two major problems for health professionals: (1) the identification and adoption of population-based prevention strategies involving healthy lifestyle beginning early in life, and, (2) the need to identify high risk obese children for targeted interventions. There is some agreement, especially in adults, that the assessment of fat distribution (visceral fat in particular), may be a useful approach for determining risk of disease associated with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that the prevalence of obesity and NAFLD in elementary school children in increas-BASIC DATA FROM THE PEDIATRIC COMPREHENSIVE HEALTH CHECK ing. 12,13) Thus, to evaluate the frequency of children with lifestyle -related diseases including obesity and/or NAFLD more precisely, it is necessary to compare the number of pediatric patients with lifestyle -related diseases between the population living in the evacuation zone and the general population.…”
Section: Discussionmentioning
confidence: 99%